Transparent black PC flame-retardant material capable of being subjected to laser etching as well as preparation method and application of transparent black PC flame-retardant material
By using specific formulas and additives in PC materials, the problem of being difficult to achieve clear laser engraving and black transparent effects in the prior art is solved, and high-quality flame retardant and laser engraving effects are achieved, improving the overall performance and appearance of the product.
Patent Information
- Application Number
- CN202510074476.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to provide a PC material that can be clearly engraved and has excellent black transparency effect, especially in the fields of home appliances, smart furniture, etc., which affects the appearance and grade of the product.
By combining PC resin, silicon PC resin, flame retardant, flame retardant synergist, radium engraving additive, anti-hydrolyzer, dispersant and antioxidant, a transparent black PC flame retardant material that can be radium engraved is prepared to ensure that the material has good processability, easy moldability, flame retardancy and laser engraving effect.
It realizes the black transparent appearance of the product, has good processability and impact resistance, excellent flame retardant performance, and clear laser engraving effect, which improves the overall effect and grade of the product.
Smart Images

Figure BDA0005246647190000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer composite materials, and in particular relates to a transparent black PC flame retardant material capable of laser engraving, and a preparation method and application thereof. Background Art
[0002] As people's requirements for the quality of life increase, the requirements for the appearance of plastic products related to life are also getting higher and higher. Traditional plastic product surface patterns are usually made by silk screen printing, spraying and water transfer printing. The obtained patterns are relatively simple and single, and the durability is not strong, especially the button position. After a long time, the silk screen or spraying on the surface disappears, which makes subsequent use inconvenient. In order to obtain better physical properties and higher quality appearance effects, people have developed laser engraving technology using laser marking methods. By adding appropriate laser engraving additives, light energy is converted into heat energy, and a variety of clear patterns are obtained. It is durable, saves time, saves energy, saves the operation process of plastic product logo printing, and reduces the environmental pollution of ink chemistry compared to traditional logo processing methods. It also reduces the scrap rate of plastic products and improves the production efficiency of materials. Laser engraving technology has been successfully applied in electronic appliances, home appliances, smart furniture, cosmetics packaging, car interior buttons and door handles, dashboards, computer keyboards, glass lenses and medical devices.
[0003] Among the plastic products for daily use on the market, PC is the most high-end and diversified. Polycarbonate (PC) has high chemical stability, certain flame retardant properties, good heat resistance and transparency, and high transmittance. However, infrared light sources can directly penetrate the material, resulting in the inability to convert light energy into heat energy in large quantities, making it difficult to obtain laser engraving effects. In order to improve the laser engraving effect of the material, it is necessary to add some additives or color powders that can improve the laser engraving effect. At present, in the fields of home appliances, smart furniture, wearables and sports equipment, due to the popularization of intelligence, there are many buttons on the surface of the products, but they are all designed as touch screens. If transparent PC materials are used, the components inside can be seen during use, which affects the appearance. At the same time, the laser engraving effect on the surface of the product is not clear, which makes the overall product look ugly and reduces the grade of the product. If the product is made of transparent black, when looking from the outside to the inside, you can't see the structural parts inside, but only the shiny buttons can be seen. In this way, the overall effect of the product is very good and the grade is higher. Therefore, black, transparent and laser-engravable PC materials have become a current research hotspot.
[0004] CN 114395237A discloses a laser-engravable light-diffusing flame-retardant PC material and a preparation method thereof, but the PC material is mainly used for lampshades, and the color is mainly natural color or white.
[0005] CN 106883549 A discloses a logo-free printing plastic product and a preparation method thereof, which is mainly laser engraved into different colors. Metal powder and mica powder are added to the formula, which makes the material opaque and fails to achieve a transparent effect.
[0006] CN 107083040 A (a PC flame retardant material for laser engraving and its preparation method), CN 109423031A (a PC plastic material and its preparation method) and CN 117700976 A (a flame retardant black laser engraving PC composite material and its preparation method) respectively disclose a PC material, but the three patents only involve laser engraving and flame retardancy, not transparency, and from the formulas of the three patents, it is impossible to make a transparent material. The technical solutions in CN 114196158 A (a laser laser engraving masterbatch with a luminous effect color mark and its preparation method) and CN 117820835 A (a polycarbonate composite material and its preparation method and application) only involve laser engraving, and its materials have no flame retardancy and transparency. In CN 117700976 A (a flame retardant black laser engraving PC composite material and its preparation method), due to the addition of toughening agent and halogen flame retardant, the material made is solid color, not transparent. These technologies cannot meet the existing requirements.
[0007] Therefore, how to provide a PC material with clear laser engraving effect and excellent black transparent effect has become an urgent problem to be solved. Summary of the invention
[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a transparent black PC flame retardant material that can be laser engraved, and a preparation method and application thereof. The product provided by the present invention has a black and transparent appearance, good processability and easy formability, and has excellent flame retardancy and impact strength. The laser engraving effect is clear and can be used in a variety of life and entertainment products.
[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a transparent black PC flame retardant material that can be laser engraved. The transparent black PC flame retardant material comprises, by weight, 60-100 parts of PC resin, 10-30 parts of silicone PC resin, 0.1-1.5 parts of flame retardant, 0.1-1 parts of flame retardant synergist, 0.1-1.5 parts of laser engraving auxiliary agent, 0.05-0.5 parts of anti-hydrolysis agent, 0.1-0.5 parts of dispersant and 0.05-1 parts of antioxidant.
[0011] The molecular weight of the PC resin is 15000-19000.
[0012] The proportion of PC resin can be 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts or 90 parts, the proportion of silicone PC resin can be 10 parts, 15 parts, 20 parts, 25 parts or 30 parts, and the proportion of flame retardant can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.1 parts, 1.2 parts, 1. 3 parts, 1.4 parts or 1.5 parts, etc., the number of flame retardant synergists can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1 parts, etc., the number of laser carving additives can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.1 parts, 1.2 parts, 1 .3 parts, 1.4 parts or 1.5 parts, etc., the anti-hydrolysis agent can be 0.05 parts, 0.1 parts, 0.15 parts, 0.2 parts, 0.25 parts, 0.3 parts, 0.35 parts, 0.4 parts, 0.45 parts or 0.5 parts, etc., the dispersant can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts or 0.5 parts, etc., the antioxidant can be 0.05 parts, 0.1 parts, 0.2 parts, 0. 3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1 parts, etc., the molecular weight of the PC resin can be 15000, 15500, 16000, 16500, 17000, 17500, 18000, 17500, 18000, 18500 or 19000, etc., but are not limited to the values listed above, and other values not listed within the above numerical range.
[0013] However, it is not limited to the values listed above, and other values not listed within the above numerical range are also applicable.
[0014] The above method can effectively improve the flame retardant properties of the product by adopting flame retardants and flame retardant synergists, and can effectively improve the laser carving effect and make the laser carving pattern clearer by adopting laser carving additives; in addition, by adopting a compound of PC resin, silicone PC resin, dispersant and anti-hydrolysis agent, the synergistic effect can make the product have a black and transparent appearance, have good processability, impact resistance, and easy formability, and can effectively meet market demand.
[0015] Preferably, the silicone PC resin is a transparent silicone PC resin.
[0016] Silicone PC resin is divided into ordinary silicone PC resin and transparent silicone PC resin. Ordinary silicone PC resin is a milky white semi-transparent material, and only transparent silicone PC resin has a transparent appearance.
[0017] Preferably, the flame retardant includes any one or a combination of at least two of potassium 3-phenylsulfonylbenzenesulfonate, potassium biphenyl sulfone-3 sulfonate, bisphenol A bisdiphenyl phosphate (BDP), resorcinol bis(diphenyl phosphate) (RDP) or an organosilicon flame retardant.
[0018] Preferably, it is characterized in that the flame retardant synergist includes any one of FCA-117, FCA-107, FR-17, FR-40 or DR-M878 or a combination of at least two thereof, preferably a combination of FCA-117 and DR-M878.
[0019] The above-mentioned specific flame retardants and flame retardant synergists can effectively improve the flame retardant properties of the product without affecting the transparency.
[0020] Preferably, the laser engraving agent comprises any one of metal oxides, metal salts or laser engraving agent masterbatches or a combination of at least two of them, preferably laser engraving agent masterbatches.
[0021] Preferably, the metal oxide includes any one of copper oxide, zinc oxide or aluminum oxide, or a combination of at least two of them.
[0022] Preferably, the metal salt includes any one of copper sulfate, zinc sulfate or barium sulfate, or a combination of at least two of them.
[0023] Preferably, the laser engraving additive masterbatch is prepared by a method comprising the following steps:
[0024] The oil black is mixed with triphenyl phosphite, and then the obtained mixture is mixed with PC for granulation to obtain the laser engraving auxiliary agent masterbatch.
[0025] Preferably, the mass ratio of the oil black to triphenyl phosphite is (1-3):(2-4), wherein the number of parts of the oil black can be 1, 1.5, 2, 2.5 or 3, etc., and the number of parts of triphenyl phosphite can be 2, 2.5, 3, 3.5 or 4, etc., but are not limited to the values listed above, and other values not listed within the above numerical range are also applicable.
[0026] Preferably, the mass ratio of the mixture to PC is 1:(1-3), such as 1:1, 1:1.5, 1:2, 1:2.5 or 1:3, etc., but is not limited to the values listed above, and other values not listed within the above numerical range are also applicable.
[0027] The above-mentioned specific laser engraving auxiliary agent masterbatch can effectively improve the laser engraving effect and enhance the pattern clarity by compounding oil black and triphenyl phosphite.
[0028] Preferably, the anti-hydrolysis agent includes any one of triphenyl phosphite (TPPI), sodium acid pyrophosphate (SAPP), sodium dihydrogen phosphate (MSP, including anhydrous sodium dihydrogen phosphate AMSP) or polycarbodiimide, or a combination of at least two thereof, preferably sodium dihydrogen phosphate and / or polycarbodiimide.
[0029] The specific anti-hydrolysis agent inhibits the decomposition of the material at high temperature, significantly improves the fluidity and impact performance of the material, and has no effect on the transparency of the material.
[0030] Preferably, the dispersant comprises any one of EP wax, OP wax, montan wax, polyethylene wax or polypropylene wax, or a combination of at least two thereof, preferably montan wax.
[0031] The above-mentioned specific dispersant can fully and evenly disperse additives such as flame retardants and laser engraving masterbatches in PC resin without affecting the transparency of the material.
[0032] Preferably, the antioxidant includes antioxidant 245 and / or antioxidant 168.
[0033] In a second aspect, the present invention provides a method for preparing the transparent black PC flame retardant material as described above, the preparation method comprising the following steps:
[0034] Mixing PC resin, silicon PC resin and flame retardant synergist to obtain a first mixture; mixing flame retardant, laser engraving additive, anti-hydrolysis agent, dispersant and antioxidant to obtain a second mixture; mixing and extruding the first mixture and the second mixture to obtain the transparent black PC flame retardant material;
[0035] In a third aspect, the present invention also provides the use of the transparent black PC flame retardant material as described above in the preparation of plastic products.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] The present invention provides a transparent black PC flame retardant material capable of laser engraving. By adopting a flame retardant and a flame retardant synergist, the flame retardant performance of the product can be effectively improved. By adopting a laser engraving auxiliary agent, the laser engraving effect can be effectively improved, making the laser engraved pattern clearer. In addition, by compounding PC resin, silicon PC resin, dispersant and anti-hydrolysis agent, the synergistic effect can make the product have a black and transparent appearance, have good processability, impact resistance and easy formability, and can effectively meet market demand. DETAILED DESCRIPTION
[0038] In order to further explain the technical means and effects adopted by the present invention, the technical solution of the present invention is further described below in conjunction with the preferred embodiments of the present invention, but the present invention is not limited to the scope of the embodiments.
[0039] In the following example, PC resin IR1900: purchased from Idemitsu Corporation in Taiwan, China;
[0040] Silicone PC resin SP8010T: purchased from LG Company in South Korea;
[0041] Flame retardant bisphenol A diphenyl phosphate: purchased from Wansheng Chemical Company;
[0042] Flame retardant potassium 3-phenylsulfonylbenzenesulfonate: purchased from Dongguan Quansheng Company;
[0043] Flame retardant synergist FCA-117: purchased from Dow Corning;
[0044] Flame retardant synergist DR-M878: purchased from Yu Nuowei New Materials Co., Ltd.
[0045] Antioxidants: All purchased from BASF;
[0046] Dispersants: All purchased from Klein Corporation.
[0047] Preparation Example
[0048] This preparation example provides a laser engraving additive masterbatch, and the preparation method is as follows:
[0049] Triphenyl phosphite was added into a mixer and heated to 40°C. Then, oil black (the mass ratio of triphenyl phosphite to oil black was 3:2) was added. The mixture was stirred at 300 rpm for 10 minutes to allow the two substances to be evenly mixed to obtain a mixture. The mixture and PC material (PC-2220, Wanhua Chemical) were extruded through a twin-screw extruder at a mass ratio of 1:4 at 280°C. The produced particles were baked at 100°C for 3 hours to obtain dry laser engraving additive masterbatch.
[0050] The laser engraving additive masterbatches used in the following examples are all from the above preparation examples.
[0051] Example 1
[0052] This embodiment provides a laser-engravable transparent black PC flame-retardant material, and the raw materials for preparation (in parts by weight) are as follows:
[0053] 80 parts of PC resin, 20 parts of silicone PC resin, 0.5 parts of BDP, 0.2 parts of potassium 3-phenylsulfonylbenzenesulfonate, 0.3 parts of flame retardant synergist (FCA-117), 0.2 parts of flame retardant synergist (DR-M878), 1 part of laser carving auxiliary agent masterbatch, 0.1 parts of sodium dihydrogen phosphate, 0.2 parts of montan wax, 0.05 parts of antioxidant 245, and 0.05 parts of antioxidant 168.
[0054] The preparation method is as follows:
[0055] PC resin and flame retardant synergist are mixed to obtain mixture A; the remaining raw materials are mixed to obtain mixture B; mixture A is mixed with mixture B to obtain mixture C, and then extrusion granulation is performed using an extruder to obtain the transparent black PC flame retardant material that can be laser engraved.
[0056] Example 2
[0057] This embodiment provides a laser-engravable transparent black PC flame-retardant material, and the raw materials for preparation (in parts by weight) are as follows:
[0058] 60 parts of PC resin, 10 parts of silicone PC resin, 0.1 parts of BDP, 0.1 parts of flame retardant synergist (FCA-117), 0.1 parts of laser carving auxiliary agent masterbatch, 0.05 parts of sodium dihydrogen phosphate, 0.1 parts of montan wax, and 0.05 parts of antioxidant 245.
[0059] The preparation method is similar to that of Example 1.
[0060] Example 3
[0061] This embodiment provides a laser-engravable transparent black PC flame-retardant material, and the raw materials for preparation (in parts by weight) are as follows:
[0062] 100 parts of PC resin, 30 parts of silicone PC resin, 1 part of BDP, 0.5 parts of potassium 3-phenylsulfonylbenzenesulfonate, 1.5 parts of flame retardant synergist (FCA-117), 1 part of laser carving auxiliary agent masterbatch, 0.5 parts of sodium dihydrogen phosphate, 0.5 parts of montan wax, and 1 part of antioxidant 168.
[0063] The preparation method is similar to that of Example 1.
[0064] Example 4
[0065] This embodiment provides a laser-engravable transparent black PC flame-retardant material. The preparation method is the same as that of Embodiment 1 except that FCA-117 is replaced by an equal amount of DR-M878 in the raw materials.
[0066] The preparation method is similar to that of Example 1.
[0067] Example 5
[0068] This embodiment provides a laser-engravable transparent black PC flame-retardant material. The preparation method is the same as that of Embodiment 1 except that DR-M878 is replaced by an equal amount of FCA-117 in the raw materials.
[0069] The preparation method is similar to that of Example 1.
[0070] Example 6
[0071] This embodiment provides a transparent black PC flame retardant material that can be laser engraved. The preparation raw materials are the same as those in Example 1 except that the laser engraving auxiliary agent masterbatch is replaced with an equal amount of oil-based black.
[0072] Example 7
[0073] This embodiment provides a transparent black PC flame retardant material that can be laser engraved. The preparation raw materials are the same as those in Example 1 except that the laser engraving auxiliary agent masterbatch is replaced with an equal amount of triphenyl phosphite.
[0074] Example 8
[0075] This embodiment provides a transparent black PC flame retardant material that can be laser engraved. The preparation raw materials are the same as those in Example 1 except that the laser engraving auxiliary agent masterbatch is replaced with an equal amount of zinc oxide.
[0076] Example 9
[0077] This embodiment provides a transparent black PC flame retardant material that can be laser engraved. The preparation raw materials are the same as those in Example 1 except that the laser engraving auxiliary agent masterbatch is replaced with an equal amount of carbon black.
[0078] Example 10
[0079] This embodiment provides a laser-engravable transparent black PC flame-retardant material. The preparation method is the same as that of Embodiment 1 except that montan wax is replaced by an equal amount of polyethylene wax in the raw materials.
[0080] Comparative Example 1
[0081] This comparative example provides a laser-engravable transparent black PC flame-retardant material. The raw materials for its preparation are the same as those of Example 1, except that sodium dihydrogen phosphate is not included and a portion of the raw materials allocated to montan wax is reduced.
[0082] Comparative Example 2
[0083] This comparative example provides a laser-engravable transparent black PC flame-retardant material. The preparation raw materials are consistent with Example 1 except that montan wax is not included and a reduced portion is allocated to sodium dihydrogen phosphate.
[0084] Comparative Example 3
[0085] This comparative example provides a laser-engravable transparent black PC flame-retardant material, which is consistent with Example 1 except that the silicone PC resin is not included in the raw materials for preparation and a reduced portion is allocated to the PC resin.
[0086] Comparative Example 4
[0087] This comparative example provides a laser-engravable transparent black PC flame-retardant material, which is consistent with Example 1 except that the raw materials do not include PC resin and a reduced portion is allocated to silicone PC resin.
[0088] Effect test:
[0089] The transparent black PC flame retardant materials capable of laser engraving provided by Examples 1-10 and Comparative Examples 1-4 were tested for notched impact strength, flame retardancy, laser engraving effect and transparency. The test results are as follows:
[0090]
[0091] Note:
[0092] 1. Notched impact strength is tested according to the American testing standard ASTM-D256. The higher the value, the better the material.
[0093] 2. The flame retardancy test of the material is carried out according to the U-94 standard. The flame retardancy effect from good to bad is V0>V1>V2.
[0094] 3. Laser engraving effect: Use infrared laser engraving to engrave on the color plate and observe the clarity of the pattern.
[0095] 4. Transparency test is carried out according to the national standard GB / T 2410-2008. The higher the value, the more transparent the material.
[0096] 5. Melt index is tested according to the test standard ASTM-D1238.
[0097] From the above effects, it can be found that the product provided by the present invention has a black and transparent appearance, good processability, easy formability, good flame retardancy, excellent laser engraving effect, clear patterns, and high impact strength.
[0098] 1. By comparing Examples 1, 4-10, it can be found that the present invention can further improve the laser engraving effect of the product by selecting specific laser engraving additive masterbatch, anti-hydrolysis agent and dispersant;
[0099] 2. By comparing Example 1 and Comparative Examples 1-4, it can be found that the present invention uses a compound of PC resin, silicone PC resin, anti-hydrolysis agent and dispersant to synergistically make the product appear black and transparent, thereby improving the transparency of the material;
[0100] 3. By comparing Example 1, Examples 5-6, Examples 9-10 and Comparative Examples 1-2, it can be found that the present invention obtains a very good flame retardant effect by selecting specific flame retardant synergists FCA-117, DR-M878, potassium 3-phenylsulfonylbenzenesulfonate and silicone PC resin for compounding.
[0101] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the laser-engravable transparent black PC flame-retardant material and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0102] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0103] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
Claims
1. A laser-engravable transparent black PC flame-retardant material, characterized in that: The transparent black PC flame retardant material comprises, by weight, 60-100 parts of PC resin, 10-30 parts of silicone PC resin, 0.1-1.5 parts of flame retardant, 0.1-1 parts of flame retardant synergist, 0.1-1.5 parts of laser carving additive, 0.05-0.5 parts of anti-hydrolysis agent, 0.1-0.5 parts of dispersant and 0.05-1 parts of antioxidant; The molecular weight of the PC resin is 15000-19000.
2. The transparent black PC flame retardant material according to claim 1, characterized in that: The silicone PC resin is a transparent silicone PC resin.
3. The transparent black PC flame retardant material according to claim 1 or 2, characterized in that: The flame retardant includes any one of potassium 3-phenylsulfonylbenzenesulfonate, potassium biphenylsulfone-3 sulfonate, bisphenol A bis(diphenyl phosphate), resorcinol bis(diphenyl phosphate) or an organosilicon flame retardant or a combination of at least two thereof.
4. The transparent black PC flame retardant material according to any one of claims 1 to 3, characterized in that: The flame retardant synergist includes any one of FCA-117, FCA-107, FR-17, FR-40 or DR-M878 or a combination of at least two thereof, preferably a combination of FCA-117 and DR-M878.
5. The transparent black PC flame retardant material according to any one of claims 1 to 4, characterized in that: The laser engraving agent comprises any one of metal oxides, metal salts or laser engraving agent masterbatches or a combination of at least two of them, preferably laser engraving agent masterbatches; Preferably, the metal oxide comprises any one of copper oxide, zinc oxide or aluminum oxide, or a combination of at least two thereof; Preferably, the metal salt includes any one of copper sulfate, zinc sulfate or barium sulfate, or a combination of at least two of them.
6. The transparent black PC flame retardant material according to claim 5, characterized in that: The laser engraving auxiliary agent masterbatch is prepared by a method comprising the following steps: Mixing oil black with triphenyl phosphite, and then mixing the obtained mixture with PC to granulate to obtain the laser engraving auxiliary agent masterbatch; Preferably, the mass ratio of the oil black to triphenyl phosphite is (1-3):(2-4); Preferably, the mass ratio of the mixture to PC is 1:(1-3).
7. The transparent black PC flame retardant material according to any one of claims 1 to 6, characterized in that: The anti-hydrolysis agent includes any one of triphenyl phosphite, sodium acid pyrophosphate, sodium dihydrogen phosphate or polycarbodiimide or a combination of at least two thereof, preferably sodium dihydrogen phosphate and / or polycarbodiimide.
8. The transparent black PC flame retardant material according to any one of claims 1 to 7, characterized in that: The dispersant comprises any one of EP wax, OP wax, montan wax, polyethylene wax or polypropylene wax, or a combination of at least two thereof, preferably montan wax; Preferably, the antioxidant includes antioxidant 245 and / or antioxidant 168.
9. A method for preparing a transparent black PC flame retardant material according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: PC resin, silicon PC resin and flame retardant synergist are mixed to obtain a first mixture; flame retardant, laser engraving auxiliary agent, anti-hydrolysis agent, dispersant and antioxidant are mixed to obtain a second mixture; the first mixture and the second mixture are mixed and extruded to obtain the transparent black PC flame retardant material.
10. Use of the transparent black PC flame retardant material according to any one of claims 1 to 8 in the preparation of plastic products.
Citation Information
Patent Citations
Logo printing-free plastic product and preparation method thereof
CN106883549A
PC flame retardant material for laser engraving and preparation method thereof
CN107083040A
PC plastic cement material, and preparation method thereof
CN109423031A
Laser carving master batch with noctilucent effect and color identification and preparation method of laser carving master batch
CN114196158A
Flame-retardant black laser-etched PC composite material and preparation method thereof
CN117700976A
Cited By
Xenon lamp aging discoloration resistant siloxane PC composite material and preparation method and application thereof
CN121182173A